The fabrication and characterization of a bismuth nanoparticle modified boron doped diamond electrode and its application to the simultaneous determination of cadmium(II) and lead(II) - Toghill, K; Wildgoose, G; Moshar, A; Mulcahy, C; Compton, R (2008)
We report the simultaneous electroanalytical determination of Pb 2+ and Cd2+ by square-wave anodic stripping voltammetry (SWASV) using a bismuth nanoparticle modified boron doped diamond (Bi-BDD) electrode. Bi deposition was performed in situ with the analytes, from a solution of 0.1 mM Bi(NO3)3 in 0.1 M HClO4 (pH 1.2), and gave detection limits of 1.9 μg L-1 and 2.3 μg L -1 for Pb(II) and Cd(II) respectively. Pb2+ and Cd 2+ could not be detected simultaneously at a bare BDD electrode, whilst on a bulk Bi macro electrode (BiBE) the limits of detection for the simultaneous determination of Pb2+ and Cd2+ were ca. ten times higher. In situ atomic force microscopy (AFM) was performed to characterize the Bi nanoparticle growth on the BDD surface over a period of 120 s. The average final size of the Bi nanoparticles was 45 ± 25 nm in height with a number density on the electrode surface of ca. 7 × 10 9 np/cm2 obtained. The in situ AFM characterization suggests that the Bi nanoparticles are deposited by an "instantaneous" nucleation and growth mechanism. © 2008 Wiley-VCH Verlag GmbH and Co. KGaA.